2020
DOI: 10.3390/ijerph17207542
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Nature Activities: A Step Toward the Labor Market for Traumatized Refugees

Abstract: Background: Globally, the number of refugees is growing. For many refugees, entering the labor market in their new country of residence is challenging. Some remain forever dependent on welfare services, and this not only weakens their chances of integration, but also harms their health and well-being. Methods: This qualitative single case study focused on a group of war-stricken refugees in Denmark. The study investigated the impact of an eight-month horticultural vocational program aimed at improving their ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…Hence, a holistic understanding of health, including nature, needs to be harnessed ( Eriksson, 2002 ). The concept of a “human being” includes the relation to oneself, to others, and nature, these relationships facilitating therapeutic processes, such as reducing stress from psychosocial disorders ( Corazon et al, 2019 ) and isolation among refugees ( Poulsen et al, 2020 ). When nature and gardens have such a health-promoting influence on human beings of all ages, we find it necessary to bring a new nature approach into nursing that includes gardens, and we should let the resident’s voice guide individual care.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a holistic understanding of health, including nature, needs to be harnessed ( Eriksson, 2002 ). The concept of a “human being” includes the relation to oneself, to others, and nature, these relationships facilitating therapeutic processes, such as reducing stress from psychosocial disorders ( Corazon et al, 2019 ) and isolation among refugees ( Poulsen et al, 2020 ). When nature and gardens have such a health-promoting influence on human beings of all ages, we find it necessary to bring a new nature approach into nursing that includes gardens, and we should let the resident’s voice guide individual care.…”
Section: Discussionmentioning
confidence: 99%
“…Björn et al (2013) took a salutogenic approach in running family therapy sessions and found that cohesive family narratives about traumatic experiences and their new lives emerged. A recent study in Denmark (Poulsen et al, 2020) uses the salutogenic approach to explore how the natural environment and participation in an eco-village can help severely traumatised refugees. Horticultural activities and respectful attitude of staff contributed to recovery while new skills were achieved, and feelings of isolation decreased (Poulsen et al, 2020, p. 1).…”
Section: Salutogenesis and Refugeesmentioning
confidence: 99%
“…Understanding how flexibility in expectations can enhance SOC (Slootjes et al, 2017) provides a pathway for interventions that strengthen SOC. Another innovative approach to the holistic health and well-being of refugees is training in horticultural skills within eco-villages (Poulsen et al, 2020). It is often qualitative studies that allow innovative use of salutogenesis in the study of refugees.…”
Section: How Does Salutogenesis Contribute To Research With Refugees?mentioning
confidence: 99%
“…Increasing numbers of studies indicate the positive health impact of green spaces on various groups of people, for example elderly people [3], teenagers [4], war veterans [5], immigrants [6], and people with eating disorders [7]. However, one group of people has largely been overlooked in the research field of nature and human health relationship [8]-people with disabilities.…”
Section: Landscape Architecture and 'Leave No One Behind'mentioning
confidence: 99%